Effects of microplastics on growth and metabolism of rice (Oryza sativa L.). (November 2022) - Ma, Jing; Aqeel, Muhammad; Khalid, Noreen; Nazir, Atia; Alzuaibr, Fahad Mohammed; Al-Mushhin, Amina A.M.; Hakami, Othman; Iqbal, Muhammad Faisal; Chen, Fu; Alamri, Saad; Hashem, Mohamed; Noman, Ali
Abstract: Present work studied the impact of different doses of polystyrene (PS) and polyvinyl chloride (PVC) microplastics (MPs) on rice plants ( Oryza sativa L.). Seven different treatments of PS and PVC MPs viz. D0 (control), D1 -D3 (0, 1.5, and 3.0 mg L −1 PS-MP) and D4 -D6 (0, 1.5, and 3.0 mg L −1 PVC-MP) were given. In the experiment, sequential variations in growth, ionic homeostasis, and antioxidant metabolism in rice were monitored. Results show that compared to control, maximum repression in shoot and root and fresh and dry weight were recorded in D6. We demonstrate that D3 and D6 reduced the photosynthetic rate up to 31.49 and 43.81% compared to D0 while the transpiration rate was enhanced only under controlled conditions. Water use efficiency and internal CO2 concentration increased due to incremented doses of MPs. Decline in photosynthetic attributes directly corresponded with reduction in SPAD value (34.96%) at D6 . Besides, ionic homeostasis was perturbed and concentration of Ca, N, P, and K in root and shoot was imbalanced due to all levels of MPs and D3 and D6 were found most hazardous for these attributes. The resultant oxidative stress caused increment in MDA (49.26 and 138.44%) and H2 O2, (66.72 and 125.18%) at D3 and D6, respectively. The maximum increase in SOD (109.08 and 146.08%), POD (232.59 and 289.23%), and CAT (182.65 and 242.89%) was estimated under D3 and D6, respectively as compared to control. Therefore, we concluded that PVC-MPs accumulation is potentially more devastating for rice growth and metabolism than PS-MPs. We recommend further research experimentats not only for translocation but also for tissue-specific retention of different sized MPs in crop plants to completely understand their influence on food safety. Graphical abstract: Image 1 Highlights: Fate and transport of MPs in terrestrial ecosystems is complex. Effects of PS-MP and PVC-MP on rice was studied. PVC-MP had a greater impact compared to PS-MP. Ionic homeostasis was affected at all levels of MPs. New strategies are needed to reduce MP impacts on crop plants.